Applying the Theory of Optimising Professional Life - Lesley Margaret Piko (Grounded Theory Review: An International Journal, 2014)
Glaser (2014) wrote that “the application of grounded theory (GT) is a relatively neglected topic” (p. 1) in the literature. Applying GT to purposely intervene and improve a situation is an important adjunct to our knowledge and understanding of GT. A recent workshop of family doctors and general practitioners provides a useful example. The theory of optimising professional life explains that doctors are concerned about sustainment in their career and, to resolve this concern, they implement solutions to optimise their personal situation. Sustainment is a new, overarching concept of three needs: the need for self-care to sustain well-being, the need for work interest to sustain motivation, and the need for income to sustain lifestyle. The objective of the workshop was to empower doctors to reinvent their careers using this theory. Working individually and in small groups, participants were able to analyse a problem and to identify potential solutions.